Strike slip tectonics and transtensional deformation in the Aegean region and the Hellenic arc: Preliminary results - Sakellariou, D.; Mascle, J.; Lykousis, V. (Bulletin of the Geological Society of Greece, 2013)
Recently acquired offshore seismic and swath bathymetry data from the Hellenic Arc, the Ionian Sea and the South and North Aegean Sea, including the Hellenic Volcanic Arc and the Cyclades plateau, along with geological and tectonic data from Plio-Quaternary basins exposed on the Hellenic Arc indicate that strike slip tectonics has played a major role in the southwestward extension of the Aegean crustal block, the development of the offshore neotectonic basins and the spatial distribution of the volcanic activity along the Volcanic Arc. Transtensional deformation, accommodated by (sinistral or dextral) strike slip zones and related extensional structures, prevail throughout Plio-Quaternary, since the North Anatolian Fault broke westwards into the North Aegean. Incipient collision of the Hellenic Forearc south of Crete with the Libyan promontory and consequent lateral escape tectonics led to the segmentation of the Hellenic Arc in distinct blocks, which move southwestwards independently from each other and are bounded by strike slip faults.